THE IMPLEMENTATION OF COMMUNICATIVE LANGUAGE TEACHING IN TEACHING SPEAKING AT MAN LUBUK ALUNG - Sari Rahmawati (Universitas Negeri Islam Sumatera Utara, 2025)
The purpose of this research was to investigate the implementation of Communicative Language Teaching (CLT) in teaching speaking at MAN Lubuk Alung. The subject of the study was an English teacher of Islamic Senior High School Lubuk Alung who has teaching experience for 25 years and followed certification program. The activities done by the teacher during teaching speaking was observed and matched with CLT principles. The result of the research revealed that the process of teaching speaking at MAN Lubuk Alung did not appropriate with CLT principles. What was done by the English teacher was close to traditional teaching traditional teaching method characteristics.